Antioxidant Assay of Kefir Peanut (Arachis hypogaea L.) with Variations in Concentration and Fermentation Time - Viogenta, Pratika; Khairunnisa, Amalia; Kartinah, Nani; Rahmadati, Erfiza (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Kefir is a processed beverage produced through pasteurized milk fermentation using a starter from kefir grains. These grains contain groups of lactic acid bacteria and yeast. Peanuts can be used as a raw material for kefir products and Arachis hypogaea L. has antioxidant activity due to a high nutritional content namely vegetable oil, protein, minerals, and essential fatty acids. This study aimed to determine the highest antioxidant activity with variations in concentration and time fermentation of peanut kefir (Arachis hypogaea L.). This research on the antioxidant activity test method used the DPPH method with UV-Vis spectrophotometry. The results of testing the antioxidant activity of peanut kefir with variations in the concentration of kefir grains of 0%, 1%, 2%, and 3% had IC50 values of 64.929 ppm, 57.675 ppm, 54.742 ppm, and 51.870 ppm, respectively. The one-way ANOVA test showed a significant difference between the IC50 value and the concentration of kefir grains. The highest antioxidant in 3% concentration determined the fermentation time with 0, 12, 24, 36, 48, and 60 hours variations. The results of testing the antioxidant activity of kefir peanut with variations in the fermentation time it was had IC50 values of 64.319 ppm respectively, 62.609 ppm, 59.376 ppm, 56.321 ppm, 51.870 ppm, and 51.384 ppm. The one-way ANOVA test results showed no significance in the 0 with 12 hours completion time and 48 with 60 hours. The research results on peanut kefir show that kefir grains of 3% and the duration of fermentation for 48 hours have strong antioxidant activity.